High pressure treatments combined with sodium lactate to inactivate Escherichia coli O157:H7 and spoilage microbiota in cured beef carpaccio - Masana, Marcelo Oscar; Barrio, Yanina Ximena; Palladino, Pablo Martin; Sancho, Ana Maria; Vaudagna, Sergio Ramon (2018)
High-pressure treatments (400 and 600 MPa) combined with the addition of sodium lactate (1 and 3%) were tested to reduce Escherichia coli O157:H7 (STEC O157) and spoilage microbiota contamination in a manufactured cured beef carpaccio in fresh or frozen conditions. Counts of spoilage microorganisms and STEC O157 were also examined during the curing step to prepare the carpaccio. STEC O157 counts remained almost unchanged through the curing process performed at 1 ± 1 °C for 12 days, with a small decrease in samples with 3% of sodium lactate. High-pressure treatments at 600 MPa for 5 min achieved an immediate reduction of up to 2 logarithmic units of STEC O157 in frozen carpaccio, and up to 1.19 log in fresh condition. Counts of spoilage bacteria diminished below detection limits in fresh or frozen carpaccio added with sodium lactate by the application of 400 and 600 MPa. Maximum injury on STEC O157 cells was observed at 600 MPa in carpaccio in fresh condition without added sodium lactate. Lethality of high-pressure treatments on STEC O157 was enhanced in frozen carpaccio, while the addition of sodium lactate at 3% reduced the lethality on STEC O157 in frozen samples, and the degree of injury in fresh carpaccio.